Molluscan Fauna and Lacustrine Sediments in Sanpete Valley Near Manti, Sanpete County; Utah - John M. Olle (Hello World!, 1969)
The aim of the study is to determine, if possible, the paleoecology of a deposit west of Manti, Utah, as well as the geomorphology of the deposit.